PENGARUH PENGENDALIAN INTERNAL TERHADAP KINERJA KARYAWAN PADA DIVISI PELAYANAN MEDIS DI RUMAH SAKIT JEMBER KLINIK - Maharani, Farisa Lailatul; Sofianti, Septarina Prita Dania; Wardayanti, Siti Maria (Universitas Jember, 2015)
This study was conducted to examine the effect of variable control environment, risk assessment, control activities, information and communication, and monitoring the performance of employees. The population in this study were all employees of the division of medical services at the Hospital Clinic Jember. The total sample for the population of employees is determined by using a formula of Taro Yamane. The number of samples used by researchers based on a calculation of the total 44 samples. Questionnaires tested the validity, reliability and test for normality. Test equipment used in this study using classic assumption test which includes heteroscedasticity test and test multicoloniarity. From the test results of multiple regression analysis produced the equation Y = 3.284 + 0.127 + 0.265 X1 X2 X3 + 0.210 + 0.129 + 0.209 X4 X5 regression equation constant positive value of 3.284, variable control environment, risk assessment, control activities, information and communication, and monitoring positive value on employee performance. T test results showed: control environment positive effect on employee performance, risk assessment positive effect on employee performance, control activities have positive influence on employee performance, information and communication positive influence on employee performance, monitoring positive influence on employee performance. The coefficient of determination that the variations that occur in the variable Y (the performance of the employee) was 85.5% determined by variable internal control, risk assessment, control activities, information and communication, and monitoring. 14.5% is determined by other variables that are unknown. KEYWORD: INTERNAL CONTROL